Г.ЕСЕМУРАТОВА ГҮРРИҢЛЕРИНДЕ ҲАЯЛ-ҚЫЗЛАР ОБРАЗЫНЫҢ ЖАСАЛЫЎЫ - Ктайбекова, З.К. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of an epic genre of Karakalpak literature a story and issues of creating images in the stories by the famous writer G.Esemuratova. There have been analyzed the women’s characters in her stories. With great artistic skill the writer describes the relation between mother and child characterized by sharp contradictions and conflicts.